2019
DOI: 10.1088/1361-6560/ab1856
|View full text |Cite
|
Sign up to set email alerts
|

NEMA NU 4-2008 and in vivo imaging performance of RAYCAN trans-PET/CT X5 small animal imaging system

Abstract: The system resolution defined as full width half maximum (FWHM) was 2.07 mm, 2.11 mm and 1.31 mm for the tangential, radial and axial resolution, respectively, at the center of the field of view. The peak noise equivalent count rate (NECR) values measured were 61 kcps at 0.19 MBq/mL for the rat size phantom and 126 kcps at 1.53 MBq/mL for the mouse size phantom. Scatter fractions were 24% and 14% for the rat and mouse phantom. The measured peak sensitivity of the system was 1.70 %. Image quality in static imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Previous studies showed that that the spatial resolution of the majority of PET scanners is slightly larger than crystal dimensions . The radial FWHM of our scanner is 2.01 at 5 mm radial offset obtained from 18 F source, which is close to or better than the corresponding values reported for FLEX Triumph X‐PET (2.0 mm), microPET R4 (2.13 mm), microPET P4 (2.29 mm), Mosaic HP (2.32 mm), ClairvivoPET (2.16 mm), and Trans‐PET/CT X5 (2.11) with approximately similar crystal dimensions. The effective transaxial resolution of our prototype is 2.02 at 5 mm radial distance whereas the ratio of the effective transverse resolution to the crystal size is about 1.02, which is in line with those reported for the microPET P4 (1.02), microPET Focus 120 (1.18), microPET Focus 220 (1.19), Inveon (1.08), Mosaic HP (1.17), Argus (1.14) and VrPET (1.15) .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Previous studies showed that that the spatial resolution of the majority of PET scanners is slightly larger than crystal dimensions . The radial FWHM of our scanner is 2.01 at 5 mm radial offset obtained from 18 F source, which is close to or better than the corresponding values reported for FLEX Triumph X‐PET (2.0 mm), microPET R4 (2.13 mm), microPET P4 (2.29 mm), Mosaic HP (2.32 mm), ClairvivoPET (2.16 mm), and Trans‐PET/CT X5 (2.11) with approximately similar crystal dimensions. The effective transaxial resolution of our prototype is 2.02 at 5 mm radial distance whereas the ratio of the effective transverse resolution to the crystal size is about 1.02, which is in line with those reported for the microPET P4 (1.02), microPET Focus 120 (1.18), microPET Focus 220 (1.19), Inveon (1.08), Mosaic HP (1.17), Argus (1.14) and VrPET (1.15) .…”
Section: Discussionsupporting
confidence: 79%
“…The overall energy resolution of the system was about 12.4% with a mean peak to valley ratio of 43.8 at 25°C temperature and 28 V bias voltage, which is better than the Inveon (14.6%), NanoPET(19%), LabPET (25%) and Argus (26%) . Moreover, it is slightly better than recently designed LYSO/SiPM‐based systems, such as MRS‐PET (14.6%), MADPET4 (13.7%), RAYCAN (15%), Hyperion (12.7%) and scanners reported by Lee et al (13.2%), Ko et al (14.2%) and Goertzen et al (12.5%) but lower than the β‐cube PET scanner (12%) …”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations